A look into water conservation: an evaluation of landscape water regulations - Schneider, Joseph (Kansas State University, 2008)
Access to water has always been a critical and often times conflicted issue along Colorado's Front Range. With current and projected population growth in the state of Colorado it can be expected that the importance of the issue will only increase. In order to control future conflicts and costs, communities throughout Colorado have started to update and implement water conservation programs to address demand and delivery issues. A water demand category that has been commonly targeted by community water conservation programs is the designed urban landscape. This study explores the effectiveness of landscape water regulations in urban, landscaped open space as tools for water conservation. The study examines the effectiveness of landscape regulations using three landscape regulations in the city of Colorado Springs. The three landscape regulations represent city and development landscape regulations and guidelines implemented before and after 1998. The effectiveness of the three regulations is measured from the results of four evaluations (regulation composition, landscape design, landscape installation and maintenance, and landscape water use) that represent the steps necessary for the development and maintenance of water efficient landscapes. The tool of measure in the four evaluations is the application and enforcement of the research based Xeriscape principles in the codes, policies, and guidelines found in the three landscape regulations. The results indicated that regulation changes that occurred in the City Landscape Code and Policy Manual in the late 1990's effectively created water conserving landscape regulations. The post 1998 landscape regulations used a diverse combination of water-wise principles that were not only suggested by the codes, policies, and guidelines but also enforced through inspections and submittals. The diversity of water-wise principles in the regulations and the balance of citations and enforcement were the major elements that reduced water use and increased conservation in the evaluated landscape tracts.
Keywords: Xeriscape; Landscape regulations; Water conservation; Landscape guidelines; Landscape Architecture (0390); Urban and Regional Planning (0999)